Emergency management of the COVID‐19 pandemic in a vascular surgery department of a large metropolitan hospital in Italy. Preparation, escalation, de‐escalation, and normal activity. Issue 5 (16th September 2020) - Chiesa, Roberto; Kahlberg, Andrea; Rinaldi, Enrico; Mascia, Daniele
Abstract: Background: During the first phase of coronavirus disease‐2019 (COVID‐19) pandemic in Italy, several strategies have been taken to deal with the pandemic outbreak. Aim of the study: To report the remodeling of the Vascular Surgery Department of San Raffaele Hospital as regards the strategies of preparation, escalation, and return to normal activities during the COVID‐19 pandemic. Preparation, escalation, de‐escalation: The Regional Authority of Lombardy remodeled the hospitalization system to allocate appropriate resources to treat patients with COVID‐19 and to identify "Hub/Spoke" hospitals for highly specialized medical activities. The Hubs hospitals were required to guarantee full‐time evaluation of all patients presenting with cardiovascular diseases with an independent pathway for patients with suspect or confirmed COVID‐19 infection. San Raffaele Hospital was identified as Hub for cardiovascular emergencies and the Vascular Surgery Department was remodeled to face this epidemic situation. Surgical treatment was reserved only to symptomatic, urgent, or emergent cases. Large areas of the hospital were simultaneously reorganized to assist patients with COVID‐19. Results: During this period, 135 patients were referred to San Raffaele Vascular Surgery Department. COVID‐19 was diagnosed in 24 patients and, among them, acute limb ischemia was the most common cause of admission. At this time, the COVID‐19 trend is in decline in Italy, and the local authorities reorganized the healthcare system to return to normal activities avoiding new escalations of COVID‐19 cases. The COVID‐19 pandemic will be remembered in Lombardy as a cataclysm. Nevertheless, the HUB/spoke system has proven to be a valid model in the management of ischemic emergencies. Continuous surveillance, cooperation, coordination, and communication to effectively respond to COVID‐19 pandemic is crucial because COVID‐19 reference centers could face similar issues in the near future.